2016
DOI: 10.1097/mao.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Active Middle Ear Implantation

Abstract: Medical and technical complications and device failures have mostly occurred in the initial period of active middle ear implants (AMEI) implementation and during clinical trials or experimental procedures. All four FIMOS had technical difficulties. An important decrease in the occurrence of both medical and technical complications was observed. Application in more recent years did not show any complications and the recent device failure rates are acceptable. Magnetic resonance imaging (MRI) incompatibility sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Previous publications on the MET device have reported adverse events [13,16], although most of the events related to the 1st generation implant. Prenzeler et al [13] investigated implant survival in MET devices for 1st (T1) and 2nd (T2) generation transducers separately over an extended period of time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous publications on the MET device have reported adverse events [13,16], although most of the events related to the 1st generation implant. Prenzeler et al [13] investigated implant survival in MET devices for 1st (T1) and 2nd (T2) generation transducers separately over an extended period of time.…”
Section: Discussionmentioning
confidence: 98%
“…In general, previously published experience [13,16] has been that the medical and technical complications and device failures in 2nd generation MET devices are not uncommon. Those findings are in line with our long-term observations in relation to the latest generation MET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MET transducer is used in two different devices: the semi-implantable MET that is commercially not available anymore and the fully implantable device Carina®. The rare articles that report on the semi-implantable MET state technical problems of the earlier MET T1 generation but only few cases are mentioned regarding the latest generation devices [3, 7]. Debeaupte et al [11] make a clear distinction between different generations of Carina implants and report on implant survival after 2 years in a multicenter setting.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of time, more and more data emerged that constituted frequent technical failure of the device. Zwartenkot et al [3] reported on a technical failure rate of 9/32 over a follow-up period of up to 13 years, whereby all failures occurred within the first 2 years after implantation. Four of the 32 patients in that publication had been implanted with a Cochlear® MET (T2) since 2014, where no failure occurred so far, insinuating an improved technical long term stability of the T2 transducer compared to the T1.…”
Section: Introductionmentioning
confidence: 99%